6(x-a)=4(x-5)

Simple and best practice solution for 6(x-a)=4(x-5) equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for 6(x-a)=4(x-5) equation:


Simplifying
6(x + -1a) = 4(x + -5)

Reorder the terms:
6(-1a + x) = 4(x + -5)
(-1a * 6 + x * 6) = 4(x + -5)
(-6a + 6x) = 4(x + -5)

Reorder the terms:
-6a + 6x = 4(-5 + x)
-6a + 6x = (-5 * 4 + x * 4)
-6a + 6x = (-20 + 4x)

Solving
-6a + 6x = -20 + 4x

Solving for variable 'a'.

Move all terms containing a to the left, all other terms to the right.

Add '-6x' to each side of the equation.
-6a + 6x + -6x = -20 + 4x + -6x

Combine like terms: 6x + -6x = 0
-6a + 0 = -20 + 4x + -6x
-6a = -20 + 4x + -6x

Combine like terms: 4x + -6x = -2x
-6a = -20 + -2x

Divide each side by '-6'.
a = 3.333333333 + 0.3333333333x

Simplifying
a = 3.333333333 + 0.3333333333x

See similar equations:

| 2[6x-7(x-1)]=5x-21 | | 9x+5y=56 | | (-x)(3y)(-2x)= | | 2x^2-27X-4565=0 | | -2x-1000= | | x+3=2(y+3) | | 2(x+4)-7=3x-5(x+1) | | 8x+30y+75x+16y+4x= | | (x+3)-2(3x-7)=5x-(x+3) | | -2x-6x-113=55 | | -4.6x=-92 | | 2x^2-2x=-1 | | 4.4x+2=3.4x | | -20=4x+3(2x-2) | | 3x+4y+10+12x+y+1= | | 1x+4y=4 | | 4=2x^3+x^2-8x | | x(1+y)=a | | 20+6x(4-2)= | | 4(x+2)=6 | | 4x+5-2x=14 | | -16f-30= | | 7x-19=6x | | -9x-2x-141=68 | | -6=3(x+2) | | -17=-2+13-8n | | 5x+5y+x+8y= | | b+(-14)=15 | | 11=7+v/5 | | -3(3x-15)-(10+x)=35 | | g-3.5=-6.2 | | 16x=1-6x |

Equations solver categories